Parallel Control Structure Scheme for Load Frequency Controller Design using Direct Synthesis Approach - Anand Kumar; Md Nishat Anwar (Institute of Advanced Engineering and Science, 2020)
This paper presents load frequency controller design for a single area as well as the multi-area thermal power system using direct synthesis approach with parallel control structure (PCS) scheme. The set-point and load frequency controller has been designed for frequency regulation and maintains tie-line power within a pre-specified limit for LFC power system. The proposed controller has been implemented for single-area, two-area, and four-area thermal power system for frequency regulation. The proposed method shows impressive simulation results compared with existed control method. The robustness of the proposed method has been examined with the help maximum sensitivity and parametric variation in the nominal power system.